2013
DOI: 10.2498/cit.1002114
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Attributes with Domain Knowledge in Formal Concept Analysis

Abstract: Recent literature reports the growing interests in data analysis using Formal Concept Analysis (FCA), in which data is represented in the form of object and attribute relations. FCA analyzes and then subsequently visualizes the data based on duality called Galois connection. Attribute exploration is a knowledge acquisition process in FCA, which interactively determines the implications holding between the attributes. The objective of this paper is to demonstrate the attribute exploration to understand the depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…We must comment on the differences of our approach to the attribute exploration discussed in [15]. Attribute exploration is a manual interactive process for building the formal context and its concept lattice.…”
Section: A Combinatorial Testing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We must comment on the differences of our approach to the attribute exploration discussed in [15]. Attribute exploration is a manual interactive process for building the formal context and its concept lattice.…”
Section: A Combinatorial Testing Methodsmentioning
confidence: 99%
“…A concept lattice reduction method is proposed that successfully preserves minimum representation of the process data. An interactive process or building concept lattices called attribute exploration is discussed in [15]. Authors used existing domain experts' knowledge during the attribute exploration and demonstrated the process on two use-cases form healthcare domain.…”
Section: Related Researchmentioning
confidence: 99%
“…FCA investigates the data which depicts relationship between the set of objects and the set of attributes. Various models based on FCA are introduced (Singh, Cherukuri & Li, 2017;Annapurna & Cherukuri, 2013;Cherukuri, Dias &Vieira, 2015;Cherukuri & Srinivas, 2010;Cherukuri, 2012;Shivhare & Cherukuri, 2016; in many areas according to the need. Cognitive functionalities Bidirectional Associative Memory has been modelled using FCA (Cherukuri, Ishwarya & Loo, 2015).…”
Section: Formal Concept Analysismentioning
confidence: 99%